Comparison of medetomidine-ketamine and dexmedetomidine-ketamine anesthesia in golden-headed lion tamarins - Selmi, André Luis; Mendes, Guilherme M.; Figueiredo, Juliana P.; Barbudo-Selmi, Glenda R. [UNESP]; Lins, Bruno T. [UNESP] (My University, 2004)
The cardiovascular, respiratory, and anesthetic effects of medetomidine-ketamine (20 μg/kg bodyweight [BW] and 10 mg/kg BW) (MK group) or dexmedetomidine-ketamine (10 μg/kg BW and 10 mg/kg BW) (DK group) were studied in golden-headed lion tamarins. Heart rate decreased after administration of both combinations; this reduction was statistically greater in the DK group than in the MK group after 15 and 45 minutes. Systolic arterial pressure decreased in a similar way in both groups, except at 15 minutes, when systolic arterial pressure was significantly lower in the DK group. Diastolic arterial pressure, mean arterial pressure, respiratory rate, and rectal temperature were progressively reduced in all groups. Sedation time was significantly shorter and anesthesia time was significantly longer in the DK group compared with MK group. Anesthetic quality and analgesia scores were significantly greater at 5 and 15 minutes in the DK group compared with the MK group. The administration of dexmedetomidine-ketamine is as safe and effective as the administration of medetomidine-ketamine in tamarins.
Keywords: alpha 2 adrenergic receptor stimulating agent; dexmedetomidine; ketamine; medetomidine; vetaset; xylazine; analgesia; analgesic activity; anesthesia; breathing rate; cardiovascular effect; controlled study; diastolic blood pressure; dose time effect relation; drug efficacy; drug potentiation; drug receptor binding; drug safety; female; heart rate; lion; male; mean arterial pressure; muscle relaxation; nonhuman; rectum temperature; respiratory function; scoring system; sedation; statistical significance; systolic blood pressure; veterinary medicine; Analgesia; Anesthetics, Combined; Anesthetics, Dissociative; Animals; Blood Pressure; Callitrichinae; Dexmedetomidine; Female; Heart Rate; Hypnotics and Sedatives; Ketamine; Male; Medetomidine; Random Allocation; Respiration; Safety; Time Factors; Leontopithecus chrysomelas; Panthera leo